Análise de teses internalistas subjacentes à modelagem computacional da mente em uma perspectiva situada, incoporada e auto organizada - Pantaleão, Nathália Cristina Alves [UNESP] (2015)
This project aims to analyze and discuss internalist/representationalist theses present in the project of mechanical modeling of the mind proposed by Cognitive Science that focalize a symbolic and representacionalist aspect of the mental processes. Such theories consider that intelligent behavior is grounded on propositional knowledge created by mental representations. Contemporary philosophers and cognitive scientists (Dreyfus, 1972, 1993, Searle, 1980, 1987, Brooks,1990, 1991, 2002, Clark, 1997, 1999, 2003, 2008; Chemero 2007, 2009, 2012) have a critical view about what is proposed in the traditional Artificial Intelligence that follows a internalist paradigm because doesn't explain sufficiently many cognitive processes related to the development of skills related to smart performances, especially those involving self-organized processes (Debrun, 1996; Bresciani; D'Ottaviano, 2000) in uncontrolled environments. In this sense, Brooks (1990, 1991, 2002) argues in favor of a modeling paradigm that is incremental that takes into consideration intelligence as a set of skills developed from agent-world interactions in uncontrolled environments. We suggest, with Ryle (1949), that skills and intelligent performances are acquired and developed from dispositions that become effective/updated in the plan of action. We will try to investigate the necessary requirements to be met by models that wish to instantiate skills or intelligent performances and analyze if the models proposed by the new robotic Brooks meet such requirements.